2001
DOI: 10.1097/00004872-200107000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Role of the renal nerves in the control of renin synthesis during different sodium intakes in the rat

Abstract: The activation of renin gene expression during sodium depletion in rats is dependent on the presence of the renal nerves, while the suppression of renin gene expression during a sodium load seems to be due to the macula densa mechanism alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Thus, we conclude that salt-induced regulation of renin release and mRNA content is not primarily dependent on changes in ␤-adrenergic input. Most previous studies are in agreement with this conclusion, because neither renal denervation nor ␤-blockers prevented the rise of renin mRNA or plasma renin caused by a low-salt diet 11,12,15 nor its inhibition by high-salt intake, 12,15 though, in some studies, mostly in humans and dogs, propranolol has been found to reduce the stimulation of renin release during salt restriction to some extent. 10 Although the current data show that the absence of ␤-adrenergic input does not prevent salt regulation of renin release, pre-existing expression levels of renin appear to be an important determinant of the change in PRC and the magnitude of the response to the dietary stimulus.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Thus, we conclude that salt-induced regulation of renin release and mRNA content is not primarily dependent on changes in ␤-adrenergic input. Most previous studies are in agreement with this conclusion, because neither renal denervation nor ␤-blockers prevented the rise of renin mRNA or plasma renin caused by a low-salt diet 11,12,15 nor its inhibition by high-salt intake, 12,15 though, in some studies, mostly in humans and dogs, propranolol has been found to reduce the stimulation of renin release during salt restriction to some extent. 10 Although the current data show that the absence of ␤-adrenergic input does not prevent salt regulation of renin release, pre-existing expression levels of renin appear to be an important determinant of the change in PRC and the magnitude of the response to the dietary stimulus.…”
Section: Discussionmentioning
confidence: 77%
“…The present results are also more dramatic than those predicted on the basis of results obtained in denervated kidneys. Although most studies have reported a decrease of renal mRNA levels in denervated compared with innervated kidneys, 11,12 the findings in such studies have not been entirely uniform. 13 Furthermore, plasma renin was reported to be reduced by bilateral renal denervation in 1 study, though there was no significant change in another.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus the pharmacological inhibition of ␤ 1 -receptors results in reduced renin secretion (130,423). Similarly, renal denervation to excise sympathetic input was shown to lower renin expression (271,354), but it should be noted that renal denervation also removes the input of the sympathetic system mediated by ␣-receptors, including hemodynamic and tubular effects (335). Most notably, double-knockout mice deficient in ␤ 1 -and ␤ 2 -receptors have substantially reduced basal PRC, ϳ85% lower than that observed in wild-type controls (434).…”
Section: Neural Control Of Renin Secretionmentioning
confidence: 99%
“…However, most studies suggest that modulation of the activity of the renin system is not crucially dependent on intact ␤-adrenergic input. That is, most reports indicate that neither renal denervation nor pharmacological ␤-blockade considerably influence the stimulation of the renin system by a salt-deficient diet or its suppression by a high-salt diet (271,353,354). In some studies in humans, dogs, and rats, however, the ␤-receptor antagonist propranolol was shown to reduce the magnitude of the renin system stimulation during a salt-deprived diet (423,879).…”
Section: Neural Control Of Renin Secretionmentioning
confidence: 99%